(untitled) (Research, Society and Development, 2022)
For ANVISA, generic drugs are compounds that, at the end of the patent period of the reference medicines, use both the same active ingredient and formulation of these, as well as the tests to which they were submitted, in order to ensure the equivalent efficacy, quality and reliability. In this sense, data reveal that the profile of consumers of medicines in the pharmaceutical industry are predominantly elderly, as a result of the need for drug therapy for the most varied clinical conditions. Thus, the present study aimed, through a literature review, to discuss the difficulties related to the acceptance of generic drugs by the elderly population. During the analysis of the results, it was identified that the prescription made by a health professional, such as the doctor, is one of the major factors inherent in the resistance to adherence of geriatric drugs by the geriatric public. This adds to the skepticism encouraged by the marketing campaigns of drug brand manufacturers and to the psychological, conscious and unconscious biases, responsible for the belief that "expensier medicines have greater effectiveness". Thus, given the above, it is emphasized the importance of professional performance at the time of prescription to the patient, since a correct anamnesis and private interview can answer questions about socioeconomic factors and frequent doubts among elderly users. So that educational and communicative interventions also become essential for the acceptance of generics by geriatric patients.